Four and a half year follow up of women with dyskaryotic cervical smears. - Fletcher, A (1990)
OBJECTIVE--To determine the proportion of women with mild or moderate dyskaryosis in cervical smears who (a) progress to cervical intraepithelial neoplasia grade III or worse or (b) regress. DESIGN--Four and a half year cytological follow up study of women with mild or moderate dyskaryosis in cervical smears. SETTING--666 Women (mean age 28 (SD 8) years; range 14-74) found to have borderline, mild, or moderate dyskaryosis on routine screening. RESULTS--45 Women (6.8%) had a cone biopsy recommended on the basis of an abnormal follow up smear (severe dyskaryosis suggestive of cervical intraepithelial neoplasia grade III or invasive cancer), and in one patient cervical intraepithelial neoplasia grade III was reported in a biopsy specimen after dilatation and curettage. Life table analysis gave a 14% probability of a patient being recommended for a biopsy after four and a half years of follow up (95% confidence interval 12% to 15%). There was a significant excess incidence of invasive cancer of the cervix in the series compared with the general population (five cases observed compared with less than 0.1 expected). 157 Patients (24%) showed reversion to a normal cell pattern sustained in several smears over more than 18 months but a single negative smear was an unreliable indicator of apparent regression. Having two successive smears showing mild dyskaryosis or a smear at any time showing moderate dyskaryosis was a significant predictor of a subsequent severely dyskaryotic smear. CONCLUSIONS--Women found to have mild or moderate dyskaryosis in cervical smears should be kept under regular surveillance. The optimum management of these patients--by cytology or colposcopy--needs to be determined by randomised controlled trials.